Social Media in Controlling Tobacco Epidemic Among Adolescents and Young Adults: A Literature Review - Adi Saputra; I Gusti Agung Ayu Ari Febiyanti (Publikasi Indonesia, 2024)
This study aimed to gather information from the literature regarding the role of social media in tobacco control among adolescents and young adults, both domestically and internationally. The study utilized a literature review from articles on Google Scholar and PubMed published between 2019 and 2023. Inclusion criteria encompassed open-access articles related to interventions using social media to control tobacco consumption among adolescents and young adults, excluding modeling studies. Intervention outcomes were assessed and extracted in narrative form. Fourteen articles met the inclusion criteria (11 original research articles and 3 articles with secondary data). Research designs in the original research articles included Randomized Control Trials (RCTs) and in-depth interviews. Studies utilizing WeChat and WhatsApp demonstrated favorable intervention outcomes in delivering tobacco control messages. Peer mentoring through Instagram was also considered easily accessible for adolescents. Other social media platforms facilitating global discussions, such as Twitter, can enhance public literacy on electronic cigarettes and facilitate the implementation of electronic cigarette policies. Social media interventions in tobacco control are more readily accepted by adolescents, easily accessible, cost-effective, and provide post-intervention social support. The presence of Key Opinion Leaders (KOLs) and message-writing techniques on social media should be considered in health promotion. Research on public perceptions of tobacco control messages delivered by KOLs could be considered for further studies.